Tax Payers Consultative Year 2015: There Is a Dramaturgy? - Lauty, Puspa Ayu; Damayanti, Theresia Woro (KINERJA, 2018)
This research examines about dramaturgy of the implementation of Tax Payer Consultative Year 2015 at Kantor Pelayanan Pajak Pratama Semarang Candisari. The purpose of this rearch is to describe and analyze the implementation of Tax Payer Consultative Year 2015 policy as a dramaturgy at Kantor Pelayanan Pajak Pratama Semarang Candisari. This research is a qualitative research using descriptive analysis and interviewing techniques directly to the informant. The number of respondents in this research were 8 people. The results of this research indicate that there was dramaturgy on the implementation of Tax Payer Consultative Year 2015 at Kantor Pelayanan Pajak Pratama Semarang Candisari. Proven by the compatibility between the criterias about the behavior of dramaturgy of Tax Payer Consultative Year 2015 policy and the criterias according to the theory of dramaturgy by Goffman (1959), which is used as a reference in this research.Keywords: Dramaturgy, Tax Payer Consultative Year 2015